RETRACTED ARTICLE: MIR600HG sponges miR-125a-5p to regulate glycometabolism and cisplatin resistance of oral squamous cell carcinoma cells via mediating RNF44 - Xingguang Liu; Tengda Zhao; Zhe Yuan; Shaohua Ge (Cell Death Discovery, 2022)
Abstract There is increasing evidence that dysregulated long non-coding RNA (lncRNA) is implicated in tumorigenesis and progression. We aim to explore the role of lncRNA MIR600HG in glycometabolism and cisplatin (DDP) resistance of oral squamous cell carcinoma (OSCC) cells via regulating microRNA-125a-5p (miR-125a-5p) and RING finger 44 (RNF44). Expression of MIR600HG, miR-125a-5p, and RNF44 in OSCC clinical samples, cell lines, and DDP-resistant OSCC cells (SCC-9/DDP) was determined. In SCC-9 cells, proliferation, IC50 value of DDP, migration, invasion, and apoptosis were detected; in SCC-9/DDP cells, proliferation, IC50 value of DDP, apoptosis, glucose consumption, and production of lactic acid and ATP were evaluated. The interaction of MR600HG, miR-125a-5p, and RNF44 was verified. MIR600HG and RNF44 were upregulated while miR-125a-5p was downregulated in OSCC tissues and cell lines, and also in SCC-9/DDP cells. In SCC-9 cells, MIR600HG overexpression improved cell growth, metastasis, and inhibited cell susceptibility to DDP; in SCC-9/DDP cells, silencing of MIR600HG promoted apoptosis, improved DDP sensitivity, and inhibited cell glycolysis. Downregulation of miR-125a-5p showed the opposite effect to downregulation of MIR600HG. MIR600HG bound to miR-125a-5p and miR-125a-5p targeted RNF44. Downregulation of miR-125a-5p reversed the improvement of DDP sensitivity and the inhibition of cell glycolysis by downregulated MIR600HG on SCC-9/DDP cells. Downregulating RNF44 reversed the promotion of DDP resistance and cell glycolysis of SCC-9/DDP cells mediated by downregulation of miR-125a-5p. Collectively, our study addresses that MIR600HG downregulation elevates miR-125a-5p and reduces RNF44 expression, thereby improving DDP sensitivity and inhibiting glycolysis in DDP-resistant OSCC cells.